(untitled) - Levitt, Theodore (New York, 1974)
The book talks about three generalk topics: how to think about and get more from the products, people, and resources; how to think sensibly about and get innovation and imitation in marketing; and how to think about marketing's claim on company resources relative to other considerations which must go into charting the purposes and managing the various functions of the whole organization.
Keywords: Marketing